Income Tax and VAT Issues Concerning Lease after IFRS 16 Convergence in Indonesia - Prianto Budi Saptono; Ismail Khozen (The Indonesian Journal of Accounting Research, 2021)
This paper aims to analyze Income Tax and Value Added Tax issues on lease transactions after IFRS 16 convergence in Indonesia into PSAK 73. This paper's data collection is through in-depth interviews with informants such as an IAI accounting standards board, lecturers and academics, and Directorate General of Taxes official. We also use secondary data to enrich the analysis. We conclude that the tax authorities need to make tax policies that can provide legal certainty. As a complement, the new tax regulation needs to accommodate a more precise direction of the policy. Among the three available options, we see that realization taxation is more appropriate for the Indonesian situation than mark-to-market or hybrid taxation. To narrow the practical gap between accounting and tax, we recommend that tax authorities initiate a discussion with relevant stakeholders to prevent potential tax disputes in the coming years. Some issues that tax authorities need to notice are withholding tax issues when the lessee records interest expenses and transfer issues when the lessor recognizes a right-of-use asset.